Designing a Web-Based Online Thesis Guidance Application for the Computer Science Study Program, Bina Bangsa University - Hermawan, Pandu; Sunarya, Po Abas; Rakhmansyah, Mohamad (PT Mattawang Mediatama Solution, 2024)
This research aims to design a web-based online thesis guidance application for the Computer Science program to facilitate the processing of student thesis data and enhance the thesis guidance process for better completion of final thesis tasks. In the thesis guidance process of the Computer Science program, several obstacles hinder students' progress in completing their theses. These obstacles include the need for students to bring their thesis materials in physical form during conventional guidance processes. This can lead to additional issues, such as the cost of printing thesis materials for corrections by supervising professors. This research utilizes the PHP programming language with the assistance of the CodeIgniter framework and MySQL as the database. The System Development Life Cycle (SDLC) Waterfall method was employed for the software development phase of this research. This method was chosen because it is a simple and linear classic model, where the output of each stage becomes the input for the next stage. Data collection techniques in this research included observation, interviews, and literature studies. This research results in a web-based online thesis guidance application that provides convenience for both students and supervising professors in conducting thesis guidance. This application also assists the Computer Science program and its students taking thesis courses. The application is more efficient when conducted online, minimizing wasted paper printouts and saving time during the guidance period, ensuring that the thesis report can be completed promptly.